2012
DOI: 10.1258/ar.2012.120012
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography findings of swine-origin influenza A (H1N1) virus (S-OIV) infection: comparison with scrub typhus

Abstract: There was considerable overlap in HRCT findings between S-OIV infection and scrub typhus. However, S-OIV showed a distinctive peribronchovascular distribution of GGO lesions. Consolidation and bronchial wall thickening were seen more frequently in S-OIV infection, whereas interlobular septal thickening and axillary lymphadenopathy were more common in scrub typhus. Thus, CT could be helpful for differential diagnosis between S-OIV infection and scrub typhus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Radiological features are different in influenza pneumonia compared with COVID-19 and pneumomediastinum is believed to be a much less frequent complication (or never occurs) in COVID-19 pneumonia. 31,32,35,37,57 By contrast, our case report indicates that it may occur, albeit this complication may have been favored by HFNC and other conditions.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Radiological features are different in influenza pneumonia compared with COVID-19 and pneumomediastinum is believed to be a much less frequent complication (or never occurs) in COVID-19 pneumonia. 31,32,35,37,57 By contrast, our case report indicates that it may occur, albeit this complication may have been favored by HFNC and other conditions.…”
Section: Discussionmentioning
confidence: 53%
“…Spontaneous pneumomediastinum is defined as air in the mediastinum without evident causes (eg, traumatic, iatrogenic, hollow organ perforation, gas‐producing infection surgery, or any other interventions) 8 . Numerous reports 24‐56 have demonstrated that several lung infections, mainly influenza, provoke pneumomediastinum. Radiological features are different in influenza pneumonia compared with COVID‐19 and pneumomediastinum is believed to be a much less frequent complication (or never occurs) in COVID‐19 pneumonia 31,32,35,37,57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 25 papers described larger cohorts of patients for a total of 2985 patients with rickettsial diseases, and among these patients, 487 (15.97%) suffered from pleural effusion. Only in 4 of these, molecular techniques were performed to achieve the etiological diagnosis [53][54][55]; the diagnosis was made by microscopic observation of morulae within the cytoplasm of polymorph-nucleate-cells only once [56]; in the other 23 case series, the diagnosis was made by serological assays [52,53,55,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. In the last 25 years in Europe, there was only one report of pleural effusion associated with a rickettsial disease.…”
Section: Pleural Effusionmentioning
confidence: 99%